Pebbles and Peregrinatio: The Taskscape of Medieval Devotion on Inishark Island, Ireland. Issue 1 (2nd January 2018) - Lash, Ryan
Abstract : SINCE 2008, the island of Inishark, Co Galway, Ireland, has been the subject of archaeological research by the Cultural Landscapes of the Irish Coast (CLIC) project, directed by Ian Kuijt of the University of Notre Dame. The CLIC project's excavations have produced new evidence for the use of water-smoothed pebbles within monastic and pilgrimage practices on the island. Using a relational perspective centred on the concept of 'taskscape', this article traces the formation, acquisition, manipulation, and deposition of these pebbles by human and non-human agencies and suggests how the stones may have facilitated worshippers' embodiment of penitential devotion —peregrinatio — by evoking the divine governance of hydrological forces. Relational theory, although inspired by non-Western indigenous perspectives, is shown to be effective in shedding light on the interplay of bodies, language, objects, and environmental phenomena in early medieval and medieval Irish Christian practice.